Tradisi Pendidikan Nahdhatul Ulama - Daulay, Muhammad Roihan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to find out how the tradition of Nahdlatul Ulama scholars in the field of education in the Tabagsel. This research method is qualitative research with a phenomenological approach. The instrument used in this research is descriptive analysis. Collecting data obtained from the field and then carried out data classification. The classified data is then processed and analyzed based on what is found according to the point of view. From this analysis, an analysis is carried out by confirming the findings related to the data which will be discussed in detail in a result and discussion. The results of the study indicate that the tradition of the ulama in the Nahdlatul Ulama organization has gone hand in hand with the times. The tradition of the ulama in the Nahdhatul Ulama organization, especially in the field of education. Researcher suggestions for the development of educational institutions need to be pursued in order to improve the quality and quantity of graduates. For researchers, it is hoped that they will continue to deepen their research at Nahdlatul Ulama, especially in the field of the educational process.